Prediction method of surface deformation around soft base dump based on viscoelastic theory - Dong WANG; Li YIN; Lanzhu CAO; Yiming FU; Liguo ZHANG; Chunhui ZHANG; Chunjian DING (Meitan kexue jishu)
Addressing the challenge of surrounding surface deformation induced by soil discharge field pile loads in weak substrates, this study delves into the mechanisms and impacts of such deformations extensively, drawing from the theory of laminar elastic systems. Employing calculus principles to differentiate the soil discharge field load and overlay the effects on the surrounding soil, coupled with considerations of substrate surface stress boundary conditions and interlayer interface continuity, the study introduces the generalized Kelvin triaxial creep model to more precisely characterize the deformation traits of weak substrates. Consequently, a methodology for addressing peripheral ground surface deformation of viscoelastic substrate soil discharge fields with rheological characteristics is derived. For the investigation, the discharging yard of the lower plate of Crooked Head Mountain Iron Mine of Bensteel Group is selected as a case study. A series of quantitative data is obtained through calculations and predictions of surface deformation on layered viscoelastic substrates under pile load actions in the discharging yard. It is observed that the settlement of piers around the discharging yard and the variation in settlement between neighboring piers gradually increase with time evolution, eventually reaching a stable state. Furthermore, in parallel sections, the settlement of the discharging yard and high-speed rail lines is 2.5 and 2.3 times respectively. The settlement in the parallel section is measured at 2.08 mm, with the maximum settlement difference of adjacent piers being 0.006 mm/m. Comparative analysis with on-site monitoring data indicates close alignment between the surface deformation analysis results and actual conditions, thereby validating the efficacy and soundness of the viscoelastic substrate's surface deformation solution around the discharging field. Notably, the analyzed values remain below normative thresholds. Further examination reveals key patterns in factors influencing surface deformation around earth displacement fields (such as slope height, angle, surface distance, and time). Notably, the distance of the earth displacement field from the slope's foot inversely correlates with surrounding surface deformation, while greater slope height and angle exacerbate deformation. Additionally, surface deformation evolves over construction time, peaking quickly before stabilizing. Overall, the findings furnish a theoretical underpinning and practical guidance for comprehending and mitigating surface deformation caused by soft substrate disposal site pile loads. The proposed solutions offer novel insights and methods for managing surface deformation in analogous projects, with the potential for positive application in engineering practice.